A Decade of Arabic Language Education Research in Indonesian Islamic Higher Education: A Bibliometric Mapping of Theses and Dissertations (2015–2024): Sepuluh Tahun Penelitian Pendidikan Bahasa Arab di Perguruan Tinggi Islam Indonesia: Pemetaan Bibliometrik Tesis dan Disertasi (2015–2024) - Maghfirah, Tadzkiratul; Himayah; Hamka (Language Development Center, 2025)
Background: Research on Arabic language education at the postgraduate level in Indonesia remains fragmented and thematically repetitive, highlighting the need for systematic mapping.. Purpose: This study aims to examine the development, thematic trends, and methodological patterns of Arabic language education research at the postgraduate level. Method: Using a descriptive bibliometric design, 113 postgraduate documents (104 master’s theses and 9 doctoral dissertations) archived in the institutional repository of UIN Alauddin Makassar between 2015 and 2024 were analyzed through total sampling. Bibliometric analysis was conducted using VOSviewer to visualize keyword co-occurrence, density, and temporal trends. Results and Discussion: The findings reveal a significant increase in research productivity, particularly in 2023–2024, with dominant themes focusing on teaching methods, learning outcomes, and digital media integration. However, thematic diversity remains limited, indicating a tendency toward topic repetition. Conclusions and Implications: These findings support the development of institutional research roadmaps, mandatory methodology training for postgraduate students, and improved repository manag